An Analysis of Semiotic Signs Found in Trailer of Quarantine Tales - Syafria, Yuni; Hidayat, Dedi; Suryani, Ririn Fitri (TALENTA, 2023)
Quarantine Tales is a film that presents various problems in the context of quarantine during the Covid-19 pandemic. This study discusses how the trailer of the film gives a semiotic sign to the audience. This qualitative study aims to describe semiotic signs in the trailer for the movie Quarantine Tales (2020). The analysis of Charles Sanders Pierce's semiotic theory is used in this study, namely the analysis using a triangle of meaning by combining representamen, objects, and interpretants. The data is screenshots from the Quarantine Tales movie trailer, which can be accessed on the official BASE Indonesia YouTube channel. Data collection methods used are documentation and observation. The results show that the meaning of representamen, objects, and interpretants is related to social, economic, and moral issues due to the COVID-19 pandemic. One of them is poverty, a prank that leads to cyberbullying, pornography, and household or family problems. In conclusion, the semiotic signs in the Quarantine Tales movie trailer provide a dramatic picture of the problems during the pandemic for the audience.